Alloimmunisation in transfused patients: serial cross-matching in a population of hospitalised cats. Issue 12 (December 2017) - Hourani, Layla; Weingart, Christiane; Kohn, Barbara
Objectives: Cross-matching is currently recommended as part of pre-transfusion testing for repeat transfusions in cats 4 days after having received an initial transfusion. This prospective study determined when and if cats developed positive cross-match (CM) results after having been transfused with AB-compatible blood. Methods: Donors were selected according to standard transfusion safety protocols. Twenty-one hospitalised anaemic recipients (blood type A: n = 20; blood type B: n = 1) received 1–4 (median 2) whole blood transfusions (WBTs) over 1–6 days (median 2) in 33 transfusion instances. The tube CM method, including major, minor and recipient control, was employed. Macroscopic and microscopic agglutination reactions were evaluated according to a predetermined scale. CM tests with a positive recipient control could not be evaluated. Results: No signs of an acute transfusion reaction were observed. A total of 63 CMs were performed. In one cat with immune-mediated haemolytic anaemia the CM could not be evaluated (positive recipient control). The minor CM was negative in all cases. Fifteen of 20 cats had a negative major CM (MCM) 1–12 days (median 5) after their first transfusion. A positive MCM was observed in five cases after 2–10 days (median 5) post-first WBT. These five cats had received a total of 1–4 (median 2) WBTs. Cats with a negative MCM had received 1–3 (median 2) WBTs. In 51.5% (17/33) of transfusion instances, the cat's haematocrit increased as expected, with cats with a positive MCM at 40% (4/10) vs 56.5% (13/23) if MCM was negative. Conclusions and relevance: Twenty-five percent (5/20) of the feline recipients likely developed alloantibodies against erythrocyte antigens outside of the AB system as early as 2 days post-first WBT. This adds data to the recommendation to include cross-matching in pre-transfusion screening tests.